Mating types and macrocyst formation in Dictyostelium. - Chang, M T (1981)
Macrocysts have been found among strains of Dictyostelium rosarium Raper and Cavender (K. B. Raper and J. C. Cavender, J. Elisha Mitchell Sci. Soc. 84:31-47, 1968). Strains that exhibit mating capabilities could be classified into one of three mating types: A1, A2, or A3. Each mating type was self-incompatible but cross-compatible with the other two types in most cases. No self-fertile strain was observed. Wet conditions, darkness, and moderate nutrient particularly favored macrocyst production; opposite conditions generally favored asexual sorocarp formation. Macrocyst development followed the same morphogenetic pattern reported previously for other species of Dictyostelium. Cultures exposed to light in stages prior to precyst appearance could be switched from macrocyst to sorocarp development. In contrast, precysts always developed into macrocysts despite the presence of light. There appeared to be an "all-or-none" phenomenon in macrocyst production, suggesting that transformation to macrocysts occurred once certain light-sensitive critical factors had reached a threshold level. Intimate association of cells of mating pairs appeared to be essential for macrocyst formation, and no mating hormones were detected.